2008
DOI: 10.1002/cjce.5450840108
|View full text |Cite
|
Sign up to set email alerts
|

Compositional Dependence of Wetting and Contact Angles in Solid-Liquid-Liquid Systems under Realistic Environments

Abstract: The Dual Drop Dual Crystal (DDDC) contact angle measurement technique has been used in this study with a high‐pressure high‐temperature optical cell apparatus to measure dynamic contact angles in rock‐oil‐brine systems at realistic reservoir conditions of temperature and pressure. The experimental observations with live, stocktank, de‐asphalted and de‐resined crude oils indicate that the stability of oil, which determines the precipitation of asphaltenes for wettability alteration, is controlled by the entire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Increasing the temperature to 90°C showed no effect on the surface wettability over 17 hours. Brine composition infl uenced the adsorption of insoluble components from crude oil onto the rock surface (Xu et al 2006). Addition of more divalent cations in the formation brine produced more positive charges on the rock surface.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing the temperature to 90°C showed no effect on the surface wettability over 17 hours. Brine composition infl uenced the adsorption of insoluble components from crude oil onto the rock surface (Xu et al 2006). Addition of more divalent cations in the formation brine produced more positive charges on the rock surface.…”
Section: Resultsmentioning
confidence: 99%
“…Addition of more divalent cations in the formation brine produced more positive charges on the rock surface. Hence, these charges acted as attractive sites for the negative ends of polar components in crude oil (Xu et al 2006 can cover the rock surface and prevent contact between the rock and crude oil. Therefore, this tendency might keep the interface neutrally charged, so that the thin wetting-water fi lm would not be disturbed by acids/bases in the crude oil.…”
Section: Resultsmentioning
confidence: 99%
“…Berea and Scioto sandstone contact angles depend on the nature of the rock. Increasing the temperature to 194ºF showed no change on the rock wettability over time duration of 17 h. Adsorption of insoluble components from crude oil on the rock surface is affected by brine composition (Xu et al 2006). Addition of more divalent cations in the formation brine resulted in more positive charges on rock surface.…”
Section: Resultsmentioning
confidence: 97%
“…This is the main reason behind having different wetting characteristics. Xu et al (2006) reported that silica (quartz and Berea) adsorbed and transferred electrons very rapidly. Seawater altered the Scioto rock surface towards water-wet condition at low and high temperature conditions.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation